Neue Ichneumoniden aus Franken (Hymenoptera: Ichneumonidae). - Bauer, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1958)
There are described the following new species of Ichneumonidae, collected by the author in Franconia (Bavaria): Coeloprosopon pectinatum, Panargyrops nigripes, Atractodes brevicornis, Glypta clypeodentata and Pion stammeri. The female of Endasys senilis Gmelin is described and established a new subgenus (Coeloprosopon) of the genus Trichocalymmus. Nomenclatural Acts brevicornis Bauer, 1958 (Atractodes), spec. n. pectinatum Bauer, 1958 (Coeloprosopon), spec. n. clypeodentata Bauer, 1958 (Glypta), spec. n. nigripes Bauer, 1958 (Panargyrops), spec. n. stammeri Bauer, 1958 (Pion), spec. n. Coeloprosopon Bauer, 1958 (Trichocalymmus), sgen. n.